Preparing the Postcolonial Situation: Polish Drugi Obieg periodicals, the Europe Topic and the Question of Poland’s Eastern Neighbors - Ritter, RÜDIGER (Porównania, 2013)
The article describes the history of the Polish underground press (referred to as second circulation) before 1989. It offers an analysis of the conditions in which the magazines appeared including conspiracy, irregular printing and instability of the editorship. The author emphasises that the Polish writers aimed at going international. They observed the changes that took place in all the countries of the communist bloc. They also wanted to modernise the society by means of introducing texts by Western authors: philosophers, politologists, historians, especially those who dealt with the phenomenon of communism.